Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Desa Wonosalam Demak - Muh. Isna Nurdin Wibisana (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Wonosalam Village is located on the banks of the Tuntang river which is the largest river in Demak. High rainfall often causes the overflow of the river to flood and cause seasonal diseases. This flood condition is exacerbated by the relatively low awareness of the community's clean life as seen from the large amount of waste that has not maintained well and the low quality of health of the residents of Wonosalam Village. The objectives of the activity are: 1) to find out the level of awareness of the community's PHBS; 2) provide practical understanding of clean and healthy life; 3) familiarize community control on PHBS, 4) improve the quality of a clean and healthy life. The methods used are surveys, lectures, discussions, and demonstrations. The results of this activity are 1) the level of understanding of residents and students as community partners regarding PHBS increases; 2) residents of Wonosalam village and students can perform several behaviors, such as washing hands with soap, exercising, brushing teeth, and carrying out proper waste disposal management; 3) residents and teachers can remind each other if there are residents or students who do not practice PHBS behavior; 4) the environment of Wonosalam villagebecomes more beautiful and clean and residents become more enthusiastic about living life.